SPECIFIC CHARACTERISTICS OF PREPARING THE FUTURE MEDICAL WORKER FOR PROFESSIONAL COMMUNICATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The development of professional competence is a relevant pedagogical issue in the conditions of Uzbekistan education system modernization. This article explaines the role and peculiarities of professional communication between a medical worker and a patient and, the hypothesis and the objectives of the research are also formulated.